2013
DOI: 10.1002/anie.201209112
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Metathesis/Iridium(I)‐catalyzed Allylic Etherification Strategy: (Iterative) Catalytic Asymmetric Synthesis of syn‐ and anti‐1,2‐Diols

Abstract: 1,2-Diol functional groups are common structures in many biologically active natural products [1] and "privileged" chiral catalysts/ligands. [2] Furthermore, 1,2-diols can serve as valuable synthetic precursors for the construction of a wide variety of other useful structures. 1,2-Diols can appear in many different forms depending on their protection state (diprotected, monoprotected, or free diol), as well as their absolute and relative stereochemistry (syn or anti). Thus, an ideal synthetic method/strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 69 publications
(34 reference statements)
2
14
0
Order By: Relevance
“…The N -allylamine product was subjected to the previously reported sequence of hydroboration, intramolecular Suzuki-Miyaura cross-coupling, and alkylation to provide (-)-angustureine. 8a The relative configuration of the product and iridium catalyst shows that the allylic substitution step of the functionalization sequence occurs with the same stereoselectivity as previously reported substitutions of allylic carbonates. 7c,15 Previously reported mechanistic studies from our group on iridium catalyzed allylic substitution reactions 7d,16 have shown that the reaction occurs by a highly diastereoselective oxidative addition of an allylic benzoate to an iridium complex 1 , followed by attack of the nucleophile onto the allyl ligand from the side opposite to the metal for all of the nucleophiles in the current study.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…The N -allylamine product was subjected to the previously reported sequence of hydroboration, intramolecular Suzuki-Miyaura cross-coupling, and alkylation to provide (-)-angustureine. 8a The relative configuration of the product and iridium catalyst shows that the allylic substitution step of the functionalization sequence occurs with the same stereoselectivity as previously reported substitutions of allylic carbonates. 7c,15 Previously reported mechanistic studies from our group on iridium catalyzed allylic substitution reactions 7d,16 have shown that the reaction occurs by a highly diastereoselective oxidative addition of an allylic benzoate to an iridium complex 1 , followed by attack of the nucleophile onto the allyl ligand from the side opposite to the metal for all of the nucleophiles in the current study.…”
Section: Resultssupporting
confidence: 66%
“…Because the iridium catalyst controls the configuration of the new stereocenter, 7e,8 the allylic substitution provides a method to control the diastereoselectivity of the amination of chiral, non-racemic alkenes. For example, the chiral alkene ( ee > 99%) containing a MOM-protected alcohol (MOM=methoxy methyl) reacted to form the substitution product 3p in 57% yield with 18:1 diastereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prominent are organocatalyzed aldol reactions of protected α‐hydroxy ketones and aldehydes11a,21 or diastereodivergent, enantioselective glycolate aldol reactions 22 . syn ‐ or anti ‐Alkenyl‐1,2‐diols can be accessed by nucleophilic addition of 3‐oxy‐substituted allylic organometallic reagents to various aldehydes with moderate to good selectivity,23 whereas anti ‐alkenyl‐1,2‐diols have been prepared through Ni‐catalyzed reductive coupling of alkynes and α‐oxy aldehydes24 or by iterative sequences of olefin cross‐metathesis and iridium(I)‐catalyzed decarboxylative allylic etherifications 25…”
Section: Introductionmentioning
confidence: 99%